DNA cleavage in immunoglobulin somatic hypermutation depends on de novo protein synthesis but not on uracil DNA glycosylase - Nagaoka, Hitoshi (National Academy of Sciences, 2005)
Activation-induced cytidine deaminase (AID) is required for the DNA cleavage step of Ig somatic hypermutation (SHM). However, its molecular mechanism is controversial. The RNA editing hypothesis postulates that AID deaminates cytosine in an unknown mRNA to generate a new mRNA encoding SHM endonuclease. On the other hand, the DNA deamination hypothesis explains DNA cleavage by cytosine deamination in DNA, followed by uracil removal by uracil DNA glycosylase (UNG). By using the protein synthesis inhibitor cycloheximide, we showed that SHM requires de novo protein synthesis in accord with predictions by the RNA editing hypothesis. In addition, we found that cycloheximide but not Ugi (the specific inhibitor of UNG) inhibited AID-dependent DNA cleavage in the Ig gene during SHM, by using histone H2AX focus formation as a marker of DNA cleavage. The results indicate the following order of events: AID expression, protein synthesis, DNA cleavage, and SHM. The requirement of protein synthesis but not of UNG for the DNA cleavage step of SHM forces us to reconsider the DNA deamination hypothesis and strengthens the RNA editing hypothesis.